Microstructure and mechanical properties of a SiC containing advanced structural ceramics. (November 2019) - Das, Jiten; Patel, Pankti; Reddy, J. Janardhana; Prasad, V.V. Bhanu
Abstract: The fracture toughness of SiC-AlN structural ceramics can be improved by obtaining fine grain size distribution of both SiC and AlN phases and a weak SiC-AlN interfacial solid solution layer which helps in crack deflection. In order to achieve this, a SiC containing ceramics i.e. 55wt.%SiC+45wt.%AlN is prepared by spark plasma sintering (1850 °C/50 MPa/5 min.). High density (96.6%) with a very fine grain microstructure comprising of intimate mixture of both the SiC and AlN phases are obtained in the product. Vol% & wt% of SiC & AlN phases estimated through the EDS mapping and Rietveld analysis are found to be 54 vol% & 46 vol%, and 54.2 wt% & 45.8 wt% respectively. Formation of solid solution layer between hexagonal AlN (a = 3.1114 Å, c = 4.9792 Å) and hexagonal SiC (a = 3.081 Å, c = 5.031 Å) phase is confirmed indirectly by change in AlN lattice parameter and directly by EDS mapping. Electron probe micro analysis (EPMA) study reveals that, the solid solution between AlN and SiC phase is formed by mainly diffusion of SiC in AlN phase. Young modulus and hardness of the SPS product are similar to those reported in the literature. The product shows higher indentation fracture toughness (6.7 ± 0.9 MPa.m 0.5 and 4.8 ± 0.6 MPa.m 0.5 obtained using Median and Palmqvist crack model respectively) than the fracture toughness of a well known ultra-high temperature structural material i.e. ZrB2–20SiC (3.9 ± 1.1 MPa.m 1/2 ). The indentation cracks are found to initiate at the AlN-SiC interface (Hv1263–1641) and are found to propagate along either the AlN phase (Hv1434–1720) or AlN-SiC interface. The cracks are found to stop when these encounter either SiC phase (Hv1896–2476) or porosity. The higher value of fracture toughness may be attributed to the mismatch in coefficient of thermal expansion (CTE) of SiC and AlN phase, fine grain size distribution, secondary crack generation and a weak AlN-SiC interfacial solid solution layer which helps in crack deflection. This product may find potential application as high temperature structural material since SiC containing materials exhibits outstanding high temperature oxidation and corrosion resistance. Highlights: High density 55SIC+45AlN material is obtained in this study by proceessing through spark plasma sintering (SPS) The SPS product shows intimate mixture of soft (Hv1434-1720) and fine AlN phase and hard(Hv1896-2476) and fine SiC phases along with numerous SiC-AlN solid solution layer at their interface which are very soft (Hv1263-1641). Presence of very fine grain size distribution of both AlN and SiC phase and numerous solid solution layer at the interface causes the tortuous crack path and secondary crack generation and improve the fracture toughness ( 5-7 MPa.m 1/2 ) of the material. As the high temperature oxidation and corrosion resitance property of the SiC-containing materials is excellent, the material can be contemplated as a potential material for ultra-high temperature application.